Pemanfaatan Bagas sebagai Bahan Baku Pembuatan Bioetanol dengan Metode Pretreatment Alkali - Daniar, Rima (ALKIMIA, 2018)
Indonesia being an agricultural country produces a large amount of cellulosic biomass such as sugarcane bagasse. This provides a low-cost feedstock for fermentative production of a wide range of fuels, economic, renewable and environmentally friendly. With utilization of renewable energy resource a crisis of energy could be solved. Sugarcane bagasse contains lignocellulose which can be broken down into glucose and produce ethanol by fermentation process. This study describes the pretreatment of sugarcane bagasse with different method of alkaline pretreatment. Sugarcane bagasse was pretreated with heating process (80oC) and without heating process (25oC) and different concentration of Alkaline (NaOH). This study also descibes the influence of fermentation time to refractive index, volume of bioethanol and % Ethanol. The alkaline pretreatment method was able to effectively increase enzymatic disgetibility of sugarcane bagasse cellulose. Based on the best result, the best condition for pretreatment to produce highest cellulose (50,71 %) was pretreatment with heating process and using NaOH 3 N. The highest refractive index was 1,3391 from 5 days fermentation. The highest volume of bioethanol was 16 ml from 7 days fermentation. The highest % etanol was 56 based on standard plot analysis method and 47,708 based on GC analysis method.